Human Laboratory Models of Cannabis Use: Applications for Clinical and Translational Psychiatry Research - Kayser, Reilly R.; Haney, Margaret; Simpson, Helen Blair (Frontiers in Psychiatry, 2021)
Cannabis is increasingly used by individuals with mental health diagnoses and often purported to treat anxiety and various other psychiatric symptoms. Yet support for using cannabis as a psychiatric treatment is currently limited by a lack of evidence from rigorous placebo-controlled studies. While regulatory hurdles and other barriers make clinical trials of cannabis challenging to conduct, addiction researchers have decades of experience studying cannabis use in human laboratory models. These include methods to control cannabis administration, to delineate clinical and mechanistic aspects of cannabis use, and to evaluate potential treatment applications for cannabis and its constituents. In this paper, we review these human laboratory procedures and describe how each can be applied to study cannabis use in patients with psychiatric disorders. Because anxiety disorders are among the most common psychiatric illnesses affecting American adults, and anxiety relief is also the most commonly-reported reason for medicinal cannabis use, we focus particularly on applying human laboratory models to study cannabis effects in individuals with anxiety and related disorders. Finally, we discuss how these methods can be integrated to study cannabis effects in other psychiatric conditions and guide future research in this area.